Perlindungan Hukum terhadap Reseller Akibat Penjual Melakukan Wanprestasi dalam Jual Beli Online : (Studi Putusan Nomor: 629/Pdt.G/2022/PN.Jkt.Sel) - Novita Sari; Jarnawi Hadi Saputra Tanjung; Apri Amalia (Lembaga Pengembangan Kinerja Dosen, 2025)
The online buying and selling system makes it easier for people to make transactions and creates business opportunities for business people to develop business transactions in collaboration with resellers without having to meet face to face, such as online buying and selling transactions for Namastudios bags. Online buying and selling transactions between suppliers and resellers are carried out by mutual agreement where the rights and obligations of the parties are regulated to avoid risks. However, there was a default in 2018 by the supplier that the goods sent did not match what was agreed. So resellers suffer quite a lot of losses. For these losses, the reseller filed a lawsuit at the South Jakarta District Court. The aim of the research is to provide legal protection and to find out the application of judges in court decision no. 629/Pdt.G/2022/PN.Jkt.Sel. The research method uses normative juridical research with a case approach which uses data collection methods through secondary data which is analyzed qualitatively. The results of the research are legal protection for resellers for default, based on Article 1320 of the Civil Code, where the agreement made is not in accordance with the agreement, it is null and void, where the supplier is obliged to compensate the reseller for losses. The application of the judge's law in the decision is that the judge granted part of the decision and stated that the Defendant had committed an act of breach of contract based on Article 1320 of the Civil Code which did not fulfill one of the conditions for the validity of the agreement, namely the agreement contained in the notarial deed.